CULTURAL HERITAGE MANAGEMENT IN AFRICA ([S.l.])
1 online resource
Keywords: Cultural Heritage Management in Africa explores the diversity of Africa's cultural heritage by analysing how and why this heritage has been managed, and by considering the factors that continue to influence management strategies and systems throughout the African continent. Including contributions from prominent scholars and heritage professionals working across Africa, the volume presents critical, contemporary perspectives on the state of heritage in the area. Chapters analyse the practices that emanated from different colonial experiences and consider what impact these had - and continue to have - on the management of African heritage. It also critically examines the ideological influence of independence movements on the African continent's management and remembering of heritage, and considers whether there are any differences in heritage management between countries that experienced armed conflicts and those that did not. The volume will be the first to critically assess the state of heritage management now, at a time when vital conversations about the balance between heritage and development is ongoing and the actions of new players have begun to impact the management and practice of heritage in the region. Cultural Heritage Management in Africa will be essential reading for those engaged in the study of museums and heritage, development, archaeology, anthropology, history and African studies. It will also be of interest to heritage and museum professionals who wish to learn more about the decolonisation of heritage.